POTENTIAL FOR ECOTOURISM DEVELOPMENT IN THE FOREST AREA OF BOJONEGORO REGENCY AS SUSTAINABLE TOURISM - Wijoyo, Handoko Sosro Hadi; Mustofa, Moh (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
There are many ways to save the forest, one of which is to make the concept of ecotourism in forest areas, both natural and socio-cultural ecotourism which is the local wisdom of residents. Local wisdom itself is the life of the village community which is one of the attractions of tourists from urban areas who have never felt village life, especially forest areas, or tourists who want to get peace in the village. In addition, the culture that is currently still believed by the forest community and has the opportunity to become a potential as a cultural heritage of the community. Ecotourism conceptualized is a form of tourism that leads to meta tourism. Ecotourism that not only sells destinations but sells philosophy. From this aspect, ecotourism will not recognize market saturation, the results of observations show that the forest area that has the potential to create Ecotourism is between two districts, namely Sekar District and Gondang District which are located in Sambongrejo, Krondonan, Klino and Deling Villages.